Construção e validação de uma cartilha educativa sobre a toxoplasmose gestacional para profissionais de saúde: estudo quasi-experimental - Cavalcante, Ulanna Maria Bastos (2021)
Toxoplasmosis is a zoonosis caused by Toxoplasma gondii and which, when reaching the woman during pregnancy, has greater relevance, due to the considerable risk of affecting the fetus. Health education represents a strategy that has the ability to prevent and reduce the risks of exposure to toxoplasmosis in pregnant women. Therefore, promoting the training of health professionals, who work in this assistance, becomes fundamental to correctly guide these women. This study consisted of investigating the knowledge about gestational toxoplasmosis among health professionals who perform prenatal care in the family health strategy, before and after exposure to the educational booklet constructed by the researcher. This study consisted of investigating the knowledge about gestational toxoplasmosis among health professionals who perform prenatal care in the family health strategy, before and after exposure to the educational booklet constructed by the researcher. It was a quasiexperimental, descriptive study, with a quanti-qualitative methodological approach. For better understanding, the study was divided into two stages: the first consisted of a methodological study (time of construction and validation of the booklet) and the second in a quasiexperimental study (time of application of the built and validated booklet, that is, intervention). Logistic regression was also applied to explain which categorical variables are relevant to the generated models. In the first model, the variables were: Toxoplasma gondii must be; reduction of vertical transmission and interpretation of IgG +/IgM+. For the second model, the following variables were obtained: conduct for IgG-/IgM+ and transmission routes. The sample related to the methodological stage had the participation of expert judges and the target audience for validation of the instruments, which after the analysis showed to have acceptable content validation. There were 6 expert judges to validate the applied questionnaire and 22 expert judges together with 16 professionals from the target audience to validate the educational booklet. The quasi-experimental stage consisted of 40 medical professionals and nurses, who worked in the health units of Cajazeiras (Intervention Group) and São José de Piranhas (Control Group), 24 professionals allocated to the intervention group and 16 to the control group. It was found that 72.5% of professionals are female, with an average age of 29.2 years, an average of 5.4 years of experience in the health area, 4.02 average (in years) of work in the health unit, with 57.5% with graduate degrees, only 2.5% had training on gestational toxoplasmosis, but 100% of professionals provide information about toxoplasmosis and 62.5% provide this information at the beginning of prenatal care. The question related to the type of treatment in pregnant women with toxoplasmosis had only 25.0% (control group) and 29.2% (intervention group) of correct answers by professionals, respectively. The means of questions answered by the intervention group were higher when compared to the control group. Regarding logistic regression, in the two models generated, the estimated parameters suggested that the variables found negatively affect knowledge. Finally, through this study, it was found that doctors and nurses in Primary Care have outdated knowledge in various aspects of gestational toxoplasmosis, compromising the good quality of prenatal care. The insertion of the educational booklet showed a significant increase in the level of knowledge of the intervention group, showing the importance that new health education strategies have within the work process of these professionals.